2012
DOI: 10.1007/s12012-012-9189-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Egyptian Sweet Marjoram (Origanum majorana L.) Leaves on Haematological Changes and Cardiotoxicity in Isoproterenol-Treated Albino Rats

Abstract: We made an attempt to evaluate/compare the cardioprotective activity of two different doses (50 and 100 mg/kg body weight, given orally for 30 consecutive days) of Egyptian sweet marjoram leaf powder (MLP) and marjoram leaf aqueous extract (MLE) against isoproterenol (ISO)-induced myocardial infarcted rats (150 mg/kg body weight, twice at an interval of 24 h on days 29 and 30). The present study showed (probably for the first time) that both MLP and MLE (especially the high dose) significantly alleviated (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Leave powder and extract significantly alleviated erythrocytosis, granulocytosis, thrombocytosis, increase heart weight, and myocardial infarction oxidative stress in isoproterenol treated albino rats. 41 Essential oil of sweet marjoram depleted serum marker enzymes and replenished antioxidant status in hepatic of rat. 10…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Leave powder and extract significantly alleviated erythrocytosis, granulocytosis, thrombocytosis, increase heart weight, and myocardial infarction oxidative stress in isoproterenol treated albino rats. 41 Essential oil of sweet marjoram depleted serum marker enzymes and replenished antioxidant status in hepatic of rat. 10…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…On the other hand, recent studies have confirmed the anti-proliferative effects of several plants such as Althaea officinalis (32,33) , Glycyrrhiza glabra L. (34,35,36) , Echium amoenum (37,38,39) , Origanum majorana (40,41) and Viola odorata (42,43,44) on viruses. Furthermore, these studies reported the antioxidant properties of Althaea officinalis (32,33) , Glycyrrhiza glabra (9,34,35,36) , Matricaria chamomilla (45,46,47) and mint (48) , the repairing effect of Althaea officinalis (32,33) and Malva sylvestris (49,50,51) and also the positive effect of Matricaria chamomilla (45,46,47) and cheese in strengthening the immune system.…”
Section: • Strengthen the Lungs And Other Involved Organsmentioning
confidence: 94%
“…74. Egyptian sweet marjoram (Origanum majorana) leaf powder and marjoram leaf aqueous extract significantly reduced erythrocytosis, granulocytosis, thrombocytosis, shortened clotting time, decrease in relative heart weight, myocardial oxidative stress and the leakage of heart enzymes (creatine phosphokinase, creatine phosphokinase-MB isoenzyme, lactate dehydrogenase, and aminotransferase) in isoproterenol treated rats through reactivating non-enzymatic (reduced glutathione) and enzymatic (catalase, glutathione peroxidase, glutathione S-transferase, and superoxide dismutase) antioxidant defense system and inhibiting the production of nitric oxide and lipid peroxidation in heart tissues [82]. 75.…”
Section: Pretreatment Of Hydroalcoholic Extract Of Ocimum Canummentioning
confidence: 99%